Budding and explosive membrane vesicle production by hypervesiculating Escherichia coli strain ΔrodZ - Ojima, Yoshihiro; Toda, Kaho; Sawabe, Tomomi; Kumazoe, Yuki; Tahara, Yuhei O.; Miyata, Makoto; Azuma, Masayuki (Frontiers in Microbiology, 2024)
Escherichia coli produces extracellular vesicles called outer membrane vesicles. In this study, we investigated the mechanism underlying the hypervesiculation of deletion mutant ΔrodZ of E. coli. RodZ forms supramolecular complexes with actin protein MreB and peptidoglycan (PG) synthase, and plays an important role in determining the cell shape. Because mreB is an essential gene, an expression-repressed strain (mreB R3 ) was constructed using CRISPRi, in which the expression of mreB decreased to 20% of that in the wild-type (WT) strain. In shaken-flask culture, the ΔrodZ strain produced >50 times more vesicles than the WT strain. The mreB-repressed strain mreB R3 showed eightfold higher vesicle production than the WT. ΔrodZ and mreB R3 cells were observed using quick-freeze replica electron microscopy. As reported in previous studies, ΔrodZ cells were spherical (WT cells are rod-shaped). Some ΔrodZ cells (around 7% in total) had aberrant surface structures, such as budding vesicles and dented surfaces, or curved patterns on the surface. Holes in the PG layer and an increased cell volume were observed for ΔrodZ and mreB R3 cells compared with the WT. In conditions of osmotic support using sucrose, the OD660 value of the ΔrodZ strain increased significantly, and vesicle production decreased drastically, compared with those in the absence of sucrose.This study first clarified that vesicle production by the E. coli ΔrodZ strain is promoted by surface budding and a burst of cells that became osmotically sensitive because of their incomplete PG structure.